Subcutaneous Panniculitis Like T Cell Lymphoma Complicated With Hemophagocytic Lymphohistiocytosis - A Challenging Case Report - Zheng, Yu-Mei; Chang, Chia-Lun; Hu, Ming-Hung; Chao, Hsiao-Mei; Whang-Peng, Jacqueline; Lai, Gi-Ming; Chiou, Tzeon-Jye (Archives of Clinical and Medical Case Reports, 2020)
Subcutaneous panniculitis-like T-cell lymphoma (SPTCL) is a rare cutaneous T-cell lymphoma which can have initial clinical manifestations of life threatening hemophagocytic lymphohistiocytosis (HLH) as complications. Due to non-specific symptoms, it can also be misdiagnosed as autoimmune diseases initially. SPTCL alone has favorable prognosis with response to chemotherapy, but its complication with HLH necessitates aggressive treatment and hematopoietic stem cell transplantation due to poor prognosis. We herein present a case of SPTCL who presented initially with clinical pictures of HLH and misdiagnosed as adult onset still's disease, the accurate diagnosis obtained diagnosed later by biopsy of delayed skin eruptions. Monitoring the HLH patients for such a rare but lethal association is thus crucial.